Coverage of Vitamin A Capsule Programme in Bangladesh and Risk Factors Associated with Non-receipt of Vitamin A (Journal of Health, Population and Nutrition, 2010)
A supplementation reduces child morbidity, mortality, and blindness. The coverage of the national vitamin A programme and risk factors for not receiving vitamin A were characterized using data from the Bangladesh Demographic and Health Survey 2004. Of 3,745 children aged 18-59 months, 3,237 (86.4%) received a vitamin A capsule each within the last six months. Children who missed vitamin A were more likely to be stunted (prevalence ratio [PR] 0.97, 95% confidence interval [CI] 0.95-1.00) and come from a family with a previous history of mortality of children aged less than five years (PR 0.95, 95% CI 0.91-0.99). Maternal education of ≥10 years (PR 1.09, 95% CI 1.04-1.13), 7-9 years (PR 1.08, 95% CI 1.04-1.12), and 1-6 years (PR 1.05, 95% CI 1.02-1.08) compared to no formal education was associated with the child not receiving vitamin A in a multivariate model, adjusting for potential confounders. Children missed by the vitamin A programme were more likely to come from families with lower maternal education. Special efforts are required to ensure that the coverage of the national vitamin A programme is increased further so that the most vulnerable children are also better protected against morbidity, mortality, and blindness. Key words: Blindness; Child; Morbidity; Mortality; Risk factors; Vitamin A; Vitamin A deficiency; Bangladesh DOI: 10.3329/jhpn.v28i2.4884 J Health Popul Nutr 2010 Apr; 28(2): 143-148